Health promoting lifestyle in educational setting: an intervention study in the universities - Rahayu, Nur Indri; Muktiarni, Muktiarni; Suherman, Adang; Ismail, Affero (Journal of Education and Learning (EduLearn), 2024)
The "health promoting universities" strategy has gained popularity and a presence in the higher education system, particularly in universities. It is imperative for higher education establishments to prioritize the promotion of health within their student body and academic community. By safeguarding and boosting students' wellbeing, a strategy centered on encouraging healthy lifestyles has the potential to boost the university's contribution to health improvement and offer significant value to the community. Universities have the power to improve health promotion through community service and to make policies in this area through research and teaching. In order to investigate student behavior in relation to the standard aspects of the healthpromoting lifestyle profile, this project will undertake an intervention study involving 150 students with the goal of promoting a healthy lifestyle. A pretest and post-test control group design was employed in this investigation. The health-promoting lifestyle standard profile II questionnaire was the research instrument, and descriptive statistics and inference were employed for analysis at the .05 significant level. The outcomes demonstrated a noteworthy impact on the implemented measures. This study's findings indicated that interventions in learning environments successfully raised student behavior linked to a healthy lifestyle and its components.